Co-occurrence of cadasil and a parkinsonian syndrome: a report of two cases and review of the literature. Issue 5 (8th May 2017) - Murray, Natalia; Pepper, Elizabeth; Blackie, Jeff; Ronan, Anne; Sugo, Ella
Abstract : Objectives: We present two patients with molecularly confirmed CADASIL presenting with a parkinsonian syndrome. CADASIL refers to Cerebral Autosomal Dominant Leukoencephalopathy with Subcortical Infarcts, an arteriopathy characterised by migraine, depression, stroke and granular deposits in vascular smooth muscle. Mutations in the NOTCH3 gene are identified in 95% patients. Isolated reports depict only a few patients with co-existing parkinsonism and CADASIL due to a number of different NOTCH3 mutations, with variable levodopa response. Methods: Brain MRI was performed in two patients presenting to a public outpatient department with a levodopa responsive parkinsonian syndrome. Analysis of the NOTCH3 gene was performed on peripheral blood lymphocytes using next generation sequencing. Autopsy including histological examination of vessels was performed on brain tissue from Patient 1. Further cases of co-existing CADASIL and Parkinsonism were identified through a search of the PubMed database. Cases: Patient 1 had been diagnosed with Parkinson's disease which was well controlled on duodopa, with a background of familial migraine, depression and anxiety. Brain MRI showed leukoencephalopathy with bilateral lacunar and frontal lobe infarcts. Genetic testing confirmed a novel c.1791G>C mutation in NOTCH3 and autopsy identified a severe leukoencephalopathy extending to the midbrain plus Lewy body deposition in the substantia nigra consistent with idiopathic Parkinson disease. Patient 2 presented at age 50 with a history of migraine, cortical and basal ganglia haemorrhage and modestly dopamine-responsive asymmetric parkinsonism. MRI confirmed leukoencephalopathy with anterior temporal lobe predominance and NOTCH3 sequencing showed a recurrent c.1261C>T mutation. Conclusions: To our knowledge this represents the first autopsy-confirmed case of CADASIL with coexistent idiopathic Parkinson's disease in a patient with a novel NOTCH3 mutation. We also report on a new genetically confirmed case of CADASIL presenting as progressive Parkinsonism.